DESIGN AND DEVELOPMENT OF EHR SPECIFIC BLOCK CREATION AND POS CUSTOMIZATION USING HIERARCHICAL INTERDEPENDENCY APPROACH - Afifa Salsabil Fathima; Syed Muzamil Basha (Malaysian Journal of Computer Science, 2023)
Electronic Health Records (EHR) serve as a pivotal component in leveraging technological capabilities for processing, diagnosis, and informed decision-making in the medical domain. The sharing and endorsement of EHR by medical professionals based on case studies undergo manual procedures, leading to limitations in global accessibility to EHR and resolved case data, impeding expert analysis. In this study, the we propose an exclusive methodology tailored for the establishment and customization of blockchain networks dedicated to EHR applications. The approach centers around a hierarchical interdependency paradigm that governs the fine-tuning of blockchain units and the creation of Proof of Stake (PoS) structures. This technique’s calibration is executed within a hospital’s private network, ensuring the generalizability of resources within the EHR context. Additionally, the technique introduces deliberate delays in the integration of federated learning models within the blockchain framework, optimizing the alignment of EHR data. Validation of the proposed technique is conducted within the framework of AWS private-public servers, utilizing a dataset sourced from 17 hospitals within the MIMIC-III public EHR dataset. The hierarchical interdependency blockchain is further harmonized with a generalized EHR setup. The study exhaustively deliberates on the outcomes of this setup, demonstrating a discernible enhancement in the performance metrics of EHR blockchains.